From Harvesting Practices to Market Orientation: Empowering Coffee Farmers through Participatory On-Farm Cupping Tests - Pratiwi, Wulan; Rahma, Melati Julia; Batoro, Jati; Faronny, Daniarry Ismail; Fatanti, Megasari Noer; Anggraeni, Asyifa; Shafira, Putri Salma; Azizah, Wanda; Bagaskara, Satria (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to describe the implementation of on-farm coffee cupping across different harvesting methods and to analyze its effects on farmers' technical practices, quality awareness, and market orientation. The program was implemented using a Participatory Action Research (PAR) approach based on six stages adapted from Saliyo's framework and delivered through an Andragogy-Based Coffee School involving 18 coffee farmers (14 men and 4 women) in collaboration with a local coffee farmers' group in Wonosalam Village. Data were collected through participatory observation, on-farm cupping using the Specialty Coffee Association (SCA) sensory evaluation protocol, and focus group discussions. Quantitative descriptive analysis was employed to visualize cup profiles using radar charts, while qualitative thematic analysis was used to examine participants' experiences and behavioral changes. The results revealed a clear relationship between harvesting methods and coffee flavor profiles. Strip picking produced flat sensory characteristics with relatively low cup quality, whereas selective picking combined with mossto fermentation generated more complex flavor profiles characterized by fruity and wine-like attributes. The program increased farmers' awareness of coffee quality, encouraged the adoption of selective harvesting and post-harvest sorting practices, and expanded market opportunities from conventional local markets to specialty and export-oriented markets. These findings suggest that participatory, experience-based learning through on-farm cupping can promote quality-oriented production practices and enhance the competitiveness of smallholder coffee farmers.